Engaging knowledge and the knower: Design considerations for emerging modes of academic staff development - Gachago, Daniela; Jones, Barbara; Esambe, Emmanuel Ekale; Jongile, Sonwabo; Ivala, Eunice (Critical Studies in Teaching and Learning, 2023)
Curriculum design is a complex undertaking that requires both epistemological and ontological work. While there is an increased need for academics to develop and strengthen their capacity to design curricula, particularly in the context of Universities of Technology, which have gone through an intense period of identity finding and re-curriculation, there is little support for academics involved in this kind of work. This paper reflects on four iterations of an academic staff development intervention aimed at supporting academics engaged in curriculum design and renewal, with a particular focus on designing flexible curricula. Using a learning design model along with eleven design considerations developed by Gachago, et al. (2020) for online academic staff development and Maton’s Legitimation Code Theory – in particular the dimension Specialization - we show how curriculum work and learning design is iterative, contextual and messy. Most importantly, it is relational and involves collective sense-making. We recommend that each context needs to be carefully considered when designing courses, both face-to-face and online, and design considerations (such as motivation, facilitation, structuredness, level of collaboration) impact strongly on participants’ engagement and consequently experiences.